Heavy Metal tolerant Non endosymbiont PGPR’s; Psuedomonas spp. and Bacillus spp. associated with the roots of evergreen shrubs Casuarinas equisetifolia - Kumar, K Vinod; Jaiprakash, C.; Punnam Chander, M.; Reesu, Rajesh; Maile, Anwesh; Lall, Chandan (Recent Research in Science and Technology, 2016)
There is a lack in research related to association of non-endosymbiont bacteria with Casuarina sp. PGPR non-endosymbiont bacteria like pseudomonas sp. and Bacillus sp. are long associated with their properties of heavy metal accumulation and plant growth promoting activity. The present study focuses on heavy metal tolerant and accumulation potential of non endosymbiont PGPR isolated from rhizosphere of Casuarina equisetifolia. The plant growth promoting properties was studied by pot culture studies on fast growing Indian moth bean Vigna aconitifolia. In the pot culture study three bacterial isolates were found to be increasing the root and shoot length by Pseudomonas sp. RS-1 (7.4±0.64 and 21.7±1.42), Bacillus sp. RS-2 (6.5±0.93 21.2±2.09) and and Bacillus sp. RS-3 (6.4±0.73 19.1±1.83) respectively. The maximum tolerance concentration of Pseudomonas sp. RS-1 shows 200 mg/L towards Cr (VI), Pb (II) 150 mg/L whereas tolerance for Cd (II), and Zn (II) were 100mg/L. Maximum % removal was shown by Bacillus sp. RS-3 towards Cr, Pb and Zn (42.51, 26.35 and 26.65 % respectively), Pseudomonas sp. RS-1 towards Cd (36.52 %). As Frankia ecological interaction between non-endosymbiont bacteria and phytoremediation ability of Casuarina sp. is not fully understood. Further study in this area may lead to better prospect in application of Casuarina as a phytoremediation agent.